Development and characterization of microsatellite markers in the African deciduous tree Terminalia superba (Combretaceae)1. (9th December 2015) - Demenou, Boris B.; Migliore, Jérémy; Tosso, Felicien; Kaymak, Esra; Hardy, Olivier J.
Abstract : Premise of the study: Microsatellites were designed and characterized in the African timber forest tree Terminalia superba (Combretaceae). Due to their high variability, these markers are suitable to investigate gene flow patterns and the structure of genetic diversity. Methods and Results: From a genomic library obtained by next‐generation sequencing, seven monomorphic and 14 polymorphic microsatellite loci were developed. The polymorphic microsatellites displayed two to 27 alleles (mean 11.4; expected heterozygosity range 0.283–0.940, mean 0.736) in one population from southeastern Cameroon. Genotypes were typical of an outbreeding diploid species, although null alleles explain a significant heterozygote deficit in three loci. Cross‐amplification in three congeneric species ( T. ivorensis, T. avicennioides, and T. mantaly ) failed, suggesting that T. superba is rather divergent. Conclusions: This set of newly developed microsatellite markers will be useful for assessing the genetic diversity, population structure, and demographic history of T. superba in tropical African forests.